Recurrent severe neutropenia following doxycycline use in a young healthy woman. Issue 3 (1st March 2022) - Foti, Michael; Shrimanker, Tushaar V.; Hasan, Umar N.; Hussein, Khalil I.
Abstract: A 29‐year‐old woman was hospitalized for fever, pharyngitis, and severe neutropenia after recent use of doxycycline and other antimicrobials. Three years later, she again presented with severe neutropenia after recent doxycycline use. Diagnostic workups were unyielding. This is only the second published case of severe neutropenia associated with doxycycline use. Abstract : Among tetracycline antibiotics, doxycycline is among the least likely to cause neutropenia. Severe neutropenia should only be attributed to doxycycline after a broad differential is considered. Filgrastim may aid recovery in neutrophil counts.